Language Style in Poetry Mahmud Sami Basha al–Barudi (A Stylistic Analysis) | Gaya Bahasa dalam Puisi Mahmud Sami Basha al–Barudi (Suatu Analisis Stilistik) - Zughrofiyatun Najah; Umi Hijriyah; Ahmad Nur Mizan; Dian Risky Amalia (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This study aims to examine the language style (al–uslub) used by al- Barudi in his poetry with the theme of life descriptions by describing the main idea or theme, elements of feeling or emotion, and language style based on aspects of diction or choice of words, syntax or sentence structure and rhetorical aspect or meaning. This research is a type of qualitative research with a descriptive-analytical literature study by referring to Al-Barudi's poetry text as the primary source. The data analysis method used is content analysis (tahlil al–madmun). The author uses a stylistic approach in examining and analyzing the language styles used by the poets in this poem. In examining this poem, the writer will use the stylistic theory proposed by Gorys Keraf related to the classification of types of diction, language style based on syntactic aspects, and rhetorical aspects or meaning. This poetry has the theme of